Training on General Journal Recording for Service Companies at SMA Kristoforus 1 Jakarta - Liana Susanto; Davin Savero; Kevin Williem (Transpublika Publisher, 2025)
Backgrounds: In the business world, especially in today’s era of globalization which is full of competition, accounting plays an important role in providing useful information to interested parties. Therefore, participating in accounting training since school is considered useful in equipping students with additional knowledge that can be useful in the world of work later on or when students continue their education to a higher level. Objectives: The primary objectives of this activity were to: (1) deliver structured training on general journal recording for service companies to high school students, and (2) quantitatively and qualitatively assess the effectiveness of this short-term intervention in improving participants’ understanding of fundamental accounting concepts. Methodology: The community service team from Tarumanagara University partnered with SMA Kristoforus 1 in Jakarta to conduct accounting training for students in grades 10–12. The training process involved four phases: a needs assessment survey to identify partner priorities, development of a targeted training module, in-school workshop implementation (beginning with foundational theory, followed by worked examples), and hands-on practice through problem-solving exercises to gauge comprehension. Findings: Post-training assessment indicated that the majority of participants demonstrated a sufficient grasp of the general journal recording material presented, confirming improved understanding of basic accounting principles. Conclusions: The short-term accounting training proved effective in enhancing students’ foundational accounting knowledge, supporting the value of early exposure to vocational skills in a school setting.